2019
DOI: 10.4062/biomolther.2018.184
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neural Stem Cell Fate by Natural Products

Abstract: Neural stem cells (NSCs) can proliferate and differentiate into multiple cell types that constitute the nervous system. NSCs can be derived from developing fetuses, embryonic stem cells, or induced pluripotent stem cells. NSCs provide a good platform to screen drugs for neurodegenerative diseases and also have potential applications in regenerative medicine. Natural products have long been used as compounds to develop new drugs. In this review, natural products that control NSC fate and induce their differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Neural stem cells (NSCs) can not only proliferate but also differentiate into neural cells such as neurons, astrocytes, and oligodendrocytes, and are therefore considered as multipotent (Kim, 2018). Some natural products like Tenuigenin (Chen Y. et al, 2012) and Incensole Acetate (El-Magd et al, 2018) have been reported to promote NSCs proliferation and increase differentiation in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Neural stem cells (NSCs) can not only proliferate but also differentiate into neural cells such as neurons, astrocytes, and oligodendrocytes, and are therefore considered as multipotent (Kim, 2018). Some natural products like Tenuigenin (Chen Y. et al, 2012) and Incensole Acetate (El-Magd et al, 2018) have been reported to promote NSCs proliferation and increase differentiation in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Neural stem cells (NSCs) are pluripotent stem cells that exist solely in the CNS. NSCs can proliferate and differentiate into multiple cell types (e.g., neurons, oligodendrocytes, and astrocytes) [154,155]. Cellular therapy makes use of neurogenic or non-neurogenic cells to improve nerve repair and tissue damage, and this method has been widely used to treat CNS diseases [155].…”
Section: Neural Stem Cell Therapymentioning
confidence: 99%
“…106 In addition, neural stem cells (NSC) can also be used as in vitro model systems for testing the efficacy of new drugs. 107 Nanofibers are employed in NSC regeneration due to their distinct configuration that support the maintenance of native tissue architecture in cultured cells. 108 The fibers offer suitable environment for the growth of NSC without interfering in their biochemical activities.…”
Section: Electrospun Nanoscaffolds In Tissue Engineeringmentioning
confidence: 99%